1982
DOI: 10.1037/0022-3514.43.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Reduced electrodermal response to conflict, failure to inhibit dominant behaviors, and delinquency proneness.

Abstract: Antisocial behavior patterns have been hypothesized to result in part from a reduced physiological component of fear, anxiety, and avoidance responses. Electrodermal correlates of antisocial personality have been consistent with such a model, but evidence that the reduced electrodermal response (EDR) of sociopathic and delinquency-prone individuals actually plays a role in their behavior is sparse. This article examines whether the reduced EDR of undersocialized individuals should be conceptualized in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 13 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…For example, Pennebaker and Chew (1985) found that deception was associated with increases in skin conductance activity, but was not related to other autonomic nervous system activity. Both as induced in the laboratory (Pennebaker & Chew, 1985;Wegner, Shortt, Blake, & Page, 1990) and as observed naturalistically (Waid & Orne, 1982;Weinberger, Scbwartz, & Davidson, 1979), inhibition has been associated witb heightened skin conductance activity. In the laboratory, subjects asked to inhibit emotionally charged thoughts, for example, thoughts of sex (Wegner et al, 1990), or to react with detachment to disturbing movie clips that depicted amputations (Koriat, Melkman, Averill, & Lazarus, 1972), showed elevated levels of skin conductance activity.…”
Section: Physiological Indicators Of Deactivation In the Attachment Imentioning
confidence: 89%
“…For example, Pennebaker and Chew (1985) found that deception was associated with increases in skin conductance activity, but was not related to other autonomic nervous system activity. Both as induced in the laboratory (Pennebaker & Chew, 1985;Wegner, Shortt, Blake, & Page, 1990) and as observed naturalistically (Waid & Orne, 1982;Weinberger, Scbwartz, & Davidson, 1979), inhibition has been associated witb heightened skin conductance activity. In the laboratory, subjects asked to inhibit emotionally charged thoughts, for example, thoughts of sex (Wegner et al, 1990), or to react with detachment to disturbing movie clips that depicted amputations (Koriat, Melkman, Averill, & Lazarus, 1972), showed elevated levels of skin conductance activity.…”
Section: Physiological Indicators Of Deactivation In the Attachment Imentioning
confidence: 89%
“…Newman and Wallace (1993) have offered an alternative to the standard "insensitivity to punishment" explanation: Psychopaths' lower anticipatory EDA represents less response uncertainty (see Schalling, 1978). That is, they engage in less prospective information processing to cope with the response conflict inherent in a mixed-incentive context (see Waid & Orne, 1982). However, their HR acceleration represents motor readiness for active coping.…”
Section: Psychopathymentioning
confidence: 99%
“…found attentional deficits in a divided attention task. Several reports~Raine & Venables, 1984;Waid, 1976;Waid & Orne, 1982! have demonstrated that low socialized participants were electrodermally hyporesponsive to a variety of stimuli.…”
Section: Psychophysiological Datamentioning
confidence: 99%